An investigation on the tribological properties of multilayer graphene and MoS2 nanosheets as additives used in hydraulic applications. (May 2016) - Zhao, Jun; He, Yongyong; Wang, Yongfu; Wang, Wei; Yan, Liang; Luo, Jianbin
Abstract: Recently, we have proposed an Electro-hydrostatic-actuator (EHA) based on a novel linear oscillating motor, which permits nanoparticle additives, such as layered graphene and MoS2, using in hydraulic oil. Especially under a super smooth (Ra 5 nm) surface unlike past studies, the tribological properties of these additives is sent more highlight. In addition, oil temperature is introduced into the friction process. We show that the friction coefficient can be decreased to as low as 0.04 when adding MoS2 nanaosheets for the chemical absorption and forming "available solid lubricant" under smooth surface and high temperature while multilayer graphene performs relatively unstable tribological properties because of agglomerates and crystal defects. It can be concluded that MoS2 nanosheets possess better potential value for the application. Highlights: Nanoparticles improving the properties of Electro-hydrostatic-actuator is proposed. The surface roughness and temperature influence on the additives are investigated. MoS2 shows better potential for the application than multilayer graphene as additives.